Contemporary Da'wah Strategy through Utilization of Artificial Intelligence (AI) - Zuhri, Syaifudin (Proceedings of International Conference on Da'wa and Communication, 2024)
The rapid development of digital technology, particularly in the field of Artificial Intelligence (AI), has opened up new opportunities for Islamic da'wah strategies in the contemporary era. This article explores how the utilization of AI can be a tool to deliver da'wah messages in a broader, personalized, and adaptive manner, as well as the challenges that arise. This study uses a qualitative research method with a desk research approach. The findings suggest that contemporary da'wah strategies incorporating AI can accelerate the spread of Islamic information by integrating AI into da'wah practices. This enables a more contextualized and interactive approach. However, proper ethical and regulatory considerations are essential to ensure that AI-assisted da'wah remains aligned with Islamic values. The implementation of AI in da'wah also faces several challenges, including low digital literacy among preachers and the potential spread of unverified Islamic information that lacks scientific authority. This article recommends strengthening digital literacy among preachers and encouraging collaboration between technology experts and clerics to develop a sustainable AI-based preaching ecosystem.